The Main Determinants of Financial Inclusion in Arab Countries - Bashar A. AL-Iragi; Sameer F. Neema (Iraqi Journal for Administrative Sciences, 2024)
The research aims to identify the main determinants of financial inclusion in the Arab countries. The research used theoretical principles and applied studies that dealt with these factors. These theoretical and applied were divided into two main trends: demand side factors (income, age, education, gender, urbanization, employment, etc.) and supply side factors (distance, regulation, Inappropriate products, risks, etc.). In addition to these two main trends, the economic, financial and legal environment of the State (institutional frameworks, legal systems, political stability, etc.) is another trend. In order to support theoretical frameworks and principles, the research used quantitative analysis based on the ARDL methodology. The Panel Data Unbalance for 17 Arab countries for the years 2011, 2014 and 2017. The research found that the variable financial structure (X8) had a positive impact on the three indicators of financial inclusion (AC) , (BC) and (SC), the income variable (X1) was positive impact in both (AC) and (SC), the education variable (X2) was negative impact in both (SC) and (BC), and the manufacturing variable (X9) was positive impact in both (SC) and (BC).